Medication Adherence, Self-Care Management and Quality of Life among Young Adults with Type 1 Diabetes Mellitus (Journal of Medical & Health Sciences Review, 2025)
The present study aimed to examine how medication adherence and self-care management predict the quality of life outcomes among young adults with type 1 diabetes mellitus. A quantitative, cross-sectional survey research design was employed. The sample size was N = 150 young adults, with n = 75 males, n = 75 females, with an age range of 18-30 years (M=24, SD=3.5) were engaged by using a non-probability purposive sampling technique. The participants demonstrated moderate levels of medication adherence (M=6.8, SD=1.2) and moderate to high levels of self-care management (M=68.4, SD=10.5), while their reported quality of life was at an average level (M=59.6, SD=8.9). Significant positive relationships were found among medication adherence with self-care management (r = .37**, p < .01) and quality of life (r = .41**, p < .01). Furthermore, self-care management emerged as the strongest predictor of quality of life (b = .48, p < .001), followed by medication adherence (b = .29, p